The Asymmetric Impulse of the Sunshine Effect on Stock Returns and Volatilities - Yuan-Ming Lee; Kuan-Min Wang (Amfiteatru Economic Journal, 2010)
This study constructs a variety of GARCH models with the consideration of the generalized error distribution to analyze the relationship between the cloud cover and stock returns in Taiwan in the whole sample period (1986 to 2007) and in the two sub-sample periods (1986 to 1996 and 1997 to 2007). The data include Taiwan Stock Exchange Capitalization Weighted Stock Index and the U.S. Dow Jones Industrial Average index to proxy the impact of U.S. stock market on Taiwan's stock market performance. The empirical finding of this study could be used to reconfirm the existence of the so-called sunshine effect. The empirical results suggest that the cloud cover has significantly negative impact on Taiwan's stock market, especially in the low cloud cover periods. Moreover, we also examine the sunshine effect with the consideration of the first and second moments and find that when adding the two moments, the sunshine effect is not significant in the stock returns but in the stock return volatilities, which is different from outcomes in previous studies.
Keywords: C22; G10; G12; 330; behavior finance; stock returns; stock volatility; Sunshine effect; Threshold model